2007
DOI: 10.1017/s0033822200042843
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Lacustrine and Wetland Sediment Accumulation Rates Determined from14C Activity of Bulk Sediment Fractions

Abstract: In the absence of identifiable macrofossils in lacustrine sediments, radiocarbon dating must rely on pollen or bulk sediment fractions. Bulk sediment fractions are not generally preferred because they contain an unknown mixture of organic material of variable age, they may contain dead carbon such as lignite that is difficult to eliminate, and material of aquatic origin may be subject to reservoir effects. If the various processes that contribute carbon to the system are relatively constant over time, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Removal of large particulate matter was done to ensure that a single large organic fragment would not disproportionately bias the 14 C activity. Samples were not pretreated because previous work at Sky Lake demonstrated that 14 C activities of bulk sediment fractions in this system are not significantly different with and without pretreatment (Walker et al 2007). Sieved samples were combusted in the presence of O 2 at 400°C (750°F).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Removal of large particulate matter was done to ensure that a single large organic fragment would not disproportionately bias the 14 C activity. Samples were not pretreated because previous work at Sky Lake demonstrated that 14 C activities of bulk sediment fractions in this system are not significantly different with and without pretreatment (Walker et al 2007). Sieved samples were combusted in the presence of O 2 at 400°C (750°F).…”
Section: Methodsmentioning
confidence: 99%
“…This age reflects a probable bias of uncertain magnitude due to incorporation of reworked material (Walker et al 2007), making it useful only as an upper limit on the possible age rather than the actual age of abandonment. A cultural resources survey by Thorne and Curry (1983) included several radiocarbon dates from Sky Lake sediment, but the reported ages varied widely without meaningful correlation with depth.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…A common difficulty in 14 C dating sediment is the presence of carbon from different sources that would give very different and misleading 14 C signatures (e.g. McGeehin et al 2001;Walker et al 2007). Sources of carbon include residual geological material (e.g.…”
Section: Introductionmentioning
confidence: 99%